Energy Evolution Behavior and Mesodamage Mechanism of Crumb Rubber Concrete - Shengtong Di; Chao Jia; Weiguo Qiao; Kang Li; Kai Tong (Advances in Materials Science and Engineering)
The energy evolution behaviour and mesodamage mechanism of CRC (crumb rubber concrete) were investigated by laboratory experiments and numerical simulations. The mesoscopic physical and mechanical parameters of CRC (crumb rubber concrete) materials were analyzed and determined by the discrete element method and trial-and-error method, and the mechanism and evolution of microcracks propagation during CRC failure were studied based on the parallel-bond model. The relationship among dissipation energy, damage threshold, and rubber content during CRC damage was studied by adopting the method of microscopic energy tracking. The energy release ratio was proposed to analyze the degree of “brittleness” of CRC after reaching its peak strength. The essential mechanism of different failure characteristics of CRC and NC (normal concrete) was analyzed and discussed by referring to their correlation between the microenergy evolution rule and the constitutive curve. The results show that (1) the calibrated mesoscopic physical and mechanical parameters can better reflect the mechanical characteristics of CRC materials, (2) there is a strong correlation between the mesoscopic damage threshold of CRC with different rubber contents and the proportion of dissipation energy at the peak strength, and the damage threshold of the CRC with 25% rubber mass is the largest, (3) the relationship between elastic strain energy release ratio of CRC and rubber particle contents can be fitted by the negative exponential function, and (4) the essential reasons for the different destruction characteristics of CRC and NC is that the addition of rubber particles makes more external input energy to be converted into dissipative energy required for microcracks propagation and sliding friction between particles and released step by step.